Early learnings from UNICEF's work to employ gender transformative approaches to advance adolescent girls' rights - Lauren Rumble; Suzanne Petroni; Ruth Graham Goulder (Child Protection and Practice)
UNICEF policies, plans, and strategies increasingly demonstrate that gender equality and the empowerment of girls are central to the organization's mandate to advance child rights. In its newest frameworks, UNICEF has pledged to practice gender transformative approaches to achieve progress toward advancing adolescent girls' wellbeing and agency, as well as a more gender equal world. Employing such approaches requires shifting power and resources to adolescent girls and girl-led organizations and networks. This means deliberate support for girls' capacities as leaders and changemakers; understanding and confronting the gendered and age-related power dynamics and norms that impede gender equality at all levels of society and stages of life; and working with girls and their communities to create more gender equitable environments for girls' rights (Rumble et al., 2022).UNICEF has seen some early successes, but also encountered challenges in applying these approaches. Gaps in expertise, restricted funding, and political sensitivities are just a few impediments to ensuring transformative action at scale. Yet, the potential impacts are enormous.In this Practice Perspective Article, we share our reflections on principles UNICEF is applying, implementation challenges it is encountering, early outcomes it is capturing, and lessons it is learning in its work to employ gender-transformative approaches to further adolescent girls’ rights.